Analisis Pendapatan dan Nilai Tambah Bandeng Gepuk Pada Industri Rumah Tangga di Kecamatan Tirtajaya Kabupaten Karawang - Silvia Jeris; Muharam Muharam; I Putu Eka Wijaya (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study has the following objectives: (1) Analyzing the income level of gepuk milkfish for one month obtained by the Gepuk Milkfish Home Industry in Tirtajaya District, Karawang Regency, (2) Analyzing the added value of gepuk milkfish for one month obtained by the Gepuk Milkfish Home Industry in Tirtajaya District, Karawang Regency. The determination of the research area was based on the consideration that, in Tirtajaya District, the raw material for milkfish is very abundant and there is processing of milkfish into gepuk milkfish. In this study, researchers set 4 people as respondents with the census method. This study uses data analysis in the form of cost, revenue, income and added value analysis. The results showed that: (1) The average total cost incurred by the processor was Rp. 26,073,441.62 per month. The average acceptance of gepuk milkfish is Rp. 44,550,000 per month. The average income is IDR 18,476,558.38 per month. (2) The added value obtained from processing milkfish into gepuk milkfish for one month is an average of IDR 8,782.17 per fish with a value added ratio of 45%. So based on these results the added value of gepuk milkfish is said to be high because it has a ratio of > 40%.